Being parent is associated with suicidal history in people with serious mental illness enrolled in psychiatric rehabilitation. (August 2021) - Dubreucq, M.; Plasse, J.; Gabayet, F.; Blanc, O.; Chereau, I.; Cervello, S.; Couhet, G.; Demily, C.; Guillard-Bouhet, N.; Gouache, B.; Jaafari, N.; Legrand, G.; et al.
Abstract: Parenting is a central life experience that could promote recovery in people with Serious Mental Illness (SMI). It could also be challenging for parents with SMI and result in poor recovery-related outcomes. Parenting is often overlooked in psychiatric rehabilitation. The objectives of the present study were to identify the characteristics and needs for care of mothers and fathers with SMI enrolled in a multicentric non-selected psychiatric rehabilitation SMI sample. We consecutively recruited 1436 outpatients from the French National Centers of Reference for Psychiatric Rehabilitation cohort (REHABase). The evaluation included standardized scales for clinical severity, psychosocial function, quality of life and satisfaction with life, wellbeing, personal recovery and a broad cognitive battery. We found that parenting was associated to suicidal history in mothers and fathers with SMI. In the multivariate analysis, being mother was best explained by insight (p < 0.015, adjusted OR = 0.76 [0.59–0.90]), current age (p < 0.001, aOR = 1.13 [1.07–1.21]), education level (p = 0.008; aOR = 0.12 [0.02–0.53]) and family accommodation (p = 0.046, aOR = 0.19 [0.03–0.84]). Being father was best explained by suicidal history (p = 0.005, aOR = 3.85 [1.51–10.10]), marital status (in relationship, p < 0.001; aOR = 7.81 [2.73–23.84]), satisfaction with family relationships (p = 0.032, aOR = 1.22 [1.02–1.47]) and current age (p < 0.001, aOR = 1.16 [1.10–1.23]). In short, parenting was associated to increased history of suicide attempt in mothers and fathers with SMI. Mothers and fathers with SMI may have unique treatment needs relating to parenting and recovery-related outcomes. The implementation of interventions supporting the needs of parents with SMI in psychiatric rehabilitation services could improve parent and children outcomes. Highlights: Parenting is often overlooked in psychiatric rehabilitation. The stress of parenting can increase suicide risk in mothers and fathers with SMI, regardless of specific diagnosis. In this sample, mothers had poorer insight and fathers showed better recovery-related outcomes. Mothers and fathers may, thus, have unique treatment needs related to parenting. Addressing parental stresses and valuing the parental role during rehabilitative treatment may facilitate personal recovery.